Perturbation Theory for Abstract Volterra Equations - Marko Kostić (Abstract and Applied Analysis)
We consider additive perturbation theorems for subgenerators of (a, k)-regularized C-resolvent families. A major part of our research is devoted to the study of perturbation properties of abstract time-fractional equations, primarily from their importance in modeling of various physical phenomena. We illustrate the results with several examples.